NEWS STORIES AND THE CREATION OF MYTHS: THE MEDIA PORTRAYAL OF LANCE ARMSTRONG AS A MODERN ICARUS - Ioana Rusu (European Scientific Journal, ESJ, 2013)
Studies on media and myth creation have argued whether mass media takes over the mythological system or mythic products appear only in certain media products, at certain periods of time. This paper enforces the perspective that all media products have a mythic status and examines the role of mass media in myth creation in modern societies through an analysis of the media framing of the cyclist Lance Armstrong as an archetypal figure. By reviewing significant events of his career and life, it is highlighted the process through which mass media portrays Lance Armstrong as a modern hero and furthermore, the role media played in his decay. After defining myth and examining how news stories are presented from the perspective of myth creation, this article analyzes the mediamyth of the modern hero created around Lance Armstrong. The research strategy involves a qualitative content analysis of a set of journalistic texts collected from the American newspaper New York Times. Nowadays, modern societies are in need of constant new creations of mythological products to relate to. The media act as storytellers and have a vital role in creating myth products that evoke archetypal figures. This paper reinforces the fact that all media products are creations having a mythic status and that the function of mass media in modern societies is similar to the function of the institutions that produced myths in ancient societies.